PTEN regulates IGF‐1R‐mediated therapy resistance in melanoma. (16th August 2015) - Wang, Jun; Sinnberg, Tobias; Niessner, Heike; Dölker, Rebecca; Sauer, Birgit; Kempf, Wolfgang E.; Meier, Friedegund; Leslie, Nick; Schittek, Birgit
Summary: Inhibition of the mitogen‐activated protein kinase (MAPK) pathway is a major advance in the treatment of metastatic melanoma. However, its therapeutic success is limited by the rapid emergence of drug resistance. The insulin‐like growth factor‐1 receptor (IGF‐1R) is overexpressed in melanomas developing resistance toward the BRAF V 600 inhibitor vemurafenib. Here, we show that hyperactivation of BRAF enhances IGF‐1R expression. In addition, the phosphatase activity of PTEN as well as heterocellular contact to stromal cells increases IGF‐1R expression in melanoma cells and enhances resistance to vemurafenib. Interestingly, PTEN‐negative melanoma cells escape IGF‐1R blockade by decreased expression of the receptor, implicating that only in melanoma patients with PTEN‐positive tumors treatment with IGF‐1R inhibitors would be a suitable strategy to combat therapy resistance. Our data emphasize the crosstalk and therapeutic relevance of microenvironmental and tumor cell‐autonomous mechanisms in regulating IGF‐1R expression and by this sensitivity toward targeted therapies.